PEDOFILIA SEBAGAI EXTRA ORDINARY CRIME PERSPEKTIF UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Kusroh Lailiyah (Journal Legal Dialectics, 2023)
Abstract This study aims to find out the factors that cause pedophilia to be considered an extraordinary crime from the perspective of Law No. 35 of 2014. This research uses a qualitative approach through descriptive analysis methods based on the study of the literature obtained and then used as material for analysis. The results of this study indicate that Law Number 35 of 2014 provides extra protection against all acts of violence. But unfortunately, sexual violence against minors or pedophilia is still thriving in Indonesia and is even increasing every year. Therefore, there must be special treatment from the state in dealing with the crime of pedophilia. There are two things that make this act of sexual violence against minors or pedophilia appropriate to be categorized as an extraordinary crime. These two things are when viewed from the consequences experienced by pedophile victims and secondly the weakness of law enforcement in Indonesia against pedophile perpetrators. Pedophilic behavior can cause victims to experience depression and even lead to death. On the other hand, the weak sentences given to pedophile perpetrators do not have a deterrent effect so that pedophile crimes in Indonesia still thrive and even continue to increase every year. Keywords: sexual violence against minors, pedophilia, child protection